Dampak bullying pada perkembangan sosial dan emosi anak - Putri, Dini Anggita (Maliki Interdisciplinary Journal, 2025)
Bullying is an act that is done repeatedly with the aim of hurting the victim and is done intentionally. Bullying can have a negative impact on children's social and emotional development. Therefore, it is necessary to prevent bullying. This article is written using the literature study method by utilising a number of journals, e-book articles obtained from the internet. The purpose of writing this article is so that readers can know the impact of bullying on children's growth and development and can prevent it.